2018
DOI: 10.1038/s41598-018-29022-4
|View full text |Cite
|
Sign up to set email alerts
|

Tidally disrupted stars as a possible origin of both cosmic rays and neutrinos at the highest energies

Abstract: Tidal Disruption Events (TDEs) are processes where stars are torn apart by the strong gravitational force near to a massive or supermassive black hole. If a jet is launched in such a process, particle acceleration may take place in internal shocks. We demonstrate that jetted TDEs can simultaneously describe the observed neutrino and cosmic ray fluxes at the highest energies if stars with heavier compositions, such as carbon-oxygen white dwarfs, are tidally disrupted and these events are sufficiently abundant. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
94
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 80 publications
(126 reference statements)
8
94
2
Order By: Relevance
“…The very hard spectra found in this case are consistent with what was found for example in Taylor et al (2015). The 3σ contours leave room for negatively evolving sources such as TDEs (Biehl et al 2018b).…”
Section: Baseline Case Characteristicssupporting
confidence: 89%
“…The very hard spectra found in this case are consistent with what was found for example in Taylor et al (2015). The 3σ contours leave room for negatively evolving sources such as TDEs (Biehl et al 2018b).…”
Section: Baseline Case Characteristicssupporting
confidence: 89%
“…However, the target photon spectrum is only measured in a small energy band and its behaviour beyond that is uncertain. In Murase et al (2016); Biehl et al (2018b), it has been shown that, depending on the spectral indices, the source can be optically thick to gamma-rays ranging from MeV to PeV. For the spectral indices we use in this work, gamma-rays even beyond PeV energies could be trapped.…”
Section: Resultsmentioning
confidence: 99%
“…The general conclusion is that the models can reproduce both the composition and energy spectrum of UHECRs (Zhang et al 2017, note that O-Ne-Mg white dwarfs lead to better agreement). The implied TDE rates range between 0.1 yr −1 Gpc −1 (Biehl et al 2018) and 10 yr −1 Gpc −1 (Alves Batista and Silk 2017) but these are inversely proportional to the baryon loading of the jets (the ratio of proton to photon luminosities) and proportional to the IMBH occupation fraction (see Section 6.3). In view of the uncertainties in these parameters, the rates reported in this paragraph are not incompatible with those of Section 6.3.…”
Section: Ultra-high Energy Cosmic Rays From Tde Jets and Other Outflowsmentioning
confidence: 99%